SISTEM POINT OF SALES (POS) BERBASIS WEBSITE DI TOKO BANGUNAN MAS BAGONG KARTASURA - Edy Susena; Dwi Iskandar; Arinda Aprilia Risnawati (LPPM Politeknik Jambi, 2023)
Mas Bagong Building Store is one of the building shops loated in Kartasura that provides various kind of building raw materials. Current problems with Mas Bagong Building Store is the diffictulty in inputting reports on sales, purchases and stock of goads. Mas Bagong Building Store uses Microsoft Exel as a dataformulas. The purpose of this research is to provide solutions to Mas Bagong Building Store owners and create a website-based Point Of Sales (POS) system that is easy for users to operate. The research method used by interview, documentasion and observation. The system development model used in this study is the Waterfall model. This method has sereval stages, namely needs analysis, design, coding, testing and implementation. After conducting a needs analysis, a POS system was designed using the Native Framework, system development using PHP and MySQL, and using XAMPP as a server. With the existence of a Point Of Sales (POS) system, it is hoped that it will simplify the process of sales, purchases and reports